Successional Dynamics in the Gut Microbiome Determine the Success of Clostridium difficile Infection in Adult Pig Models - Jurburg, Stephanie D.; Cornelissen, Jan J. B. W. J.; de Boer, Paulo; Smits, Mari A.; Rebel, Johanna M. J. (Frontiers in Cellular and Infection Microbiology, 2019)
Abstract Clostridium difficile infections (CDI) are a major cause of antibiotic-associated diarrhea. It is hypothesized that CDI develops due to the antibiotic-induced disruption of the intestinal microbial community structure, which allows C. difficile to flourish. Here, we pre-treated weaned pigs with the antibiotics Clindamycin or Ciprofloxacin for one day, and subsequently inoculated them with a human and pig enteropathogenic C. difficile strain 078 spores. Body temperature, clinical signs of disease, and the fecal microbiome were monitored daily for 15 days. Clindamycin had a stronger effect on the pigs than Ciprofloxacin, resulting in drastic shifts in the fecal microbiome, decreases in microbial diversity and significant increases in body temperature, even in the absence of C. difficile. Fecal shedding of C. difficile was detectable for 3 and 9 days in Ciprofloxacin and Clindamycin treated pigs inoculated with C. difficile, respectively, and in both cases decreased cell proliferation rates were detected in colon tissue. The timing of C. difficile shedding coincided with the decrease in a large cluster of Firmicutes following Clindamycin treatment, a pattern which was also independent of C. difficile inoculation. The observed community patterns suggest that successional dynamics following antibiotic treatment facilitate C. difficile establishment. The similarities between the microbiome responses observed in our study and those previously reported in CDI-infected humans further support the utility of adult pigs as models for the study of CDI.